Tumor Targeted Multifunctional Magnetic Nanobubbles for MR/US Dual Imaging and Focused Ultrasound Triggered Drug Delivery - Jin, Zhen; Chang, Jinlong; Dou, Peipei; Jin, Shang; Jiao, Min; Tang, Heyun; Jiang, Wenshuai; Ren, Wu; Zheng, Shaohui (Frontiers in Bioengineering and Biotechnology, 2020)
The development of multifunctional nanoplatforms that are safe and have multiple therapeutic functions integrated with dual- or multi-imaging modality is one of the most urgent medical requirements for active cancer therapy. In our study, we prepared multifunctional magnetic nanobubbles (MF-MNBs) by co-encapsulating superparamagnetic iron oxide nanoparticles (SPIONs) and doxorubicin into polylactideco–glycolide–polyethylene glycol–folate (PLGA-PEG-FA) polymer-based nanobubbles for tumor-targeted ultrasound (US)/magnetic resonance (MR) imaging and focused ultrasound (FUS)-triggered drug delivery. Hydrophobic SPIONs were successfully embedded into MF-MNBs by a typical double emulsion process. The MF-MNBs were highly dispersed with well-defined spherical morphology and an average diameter of 208.4 ± 12.58 nm. The potential of MF-MNB as a dual-modal contrast agent for US and MR imaging was investigated via in vitro study, and the MF-MNB exhibits promising US/MR contrast ability. Moreover, tumor targeting ability was further enhanced by folate conjugation and assessed through in vitro cell test. Furthermore, FUS, as a non-invasive and remote-control technique, was adopted to trigger the release of doxorubicin from MF-MNB and generate the sonoporation effect to enhance drug release and cellular uptake of MF-MNBs. The 4T1 cell viability was significantly decreased by FA ligand-receptor-mediated targeting and FUS sonication. In addition, the developed MF-MNB also exhibits enhanced accumulation in tumor site by FA ligand-receptor-mediated tumor targeting, in which the accumulation of MF-MNB was further enhanced by FUS sonication. Hence, we believe that the MF-MNB could be a promising drug nanocarrier for US/MR-guided anticancer drug delivery to improve cancer treatment efficacy.